Mouse models of telomere dysfunction phenocopy skeletal changes found in human age-related osteoporosis - Tracy A. Brennan; Kevin P. Egan; Carter M. Lindborg; Qijun Chen; Mariya T. Sweetwyne; Kurt D. Hankenson; Sharon X. Xie; Frederick B. Johnson; Robert J. Pignolo (The Company of Biologists, 2014)
A major medical challenge in the elderly is osteoporosis and the high risk of fracture. Telomere dysfunction is a cause of cellular senescence and telomere shortening, which occurs with age in cells from most human tissues, including bone. Telomere defects contribute to the pathogenesis of two progeroid disorders characterized by premature osteoporosis, Werner syndrome and dyskeratosis congenital. It is hypothesized that telomere shortening contributes to bone aging. We evaluated the skeletal phenotypes of mice with disrupted telomere maintenance mechanisms as models for human bone aging, including mutants in Werner helicase (Wrn−/−), telomerase (Terc−/−) and Wrn−/−Terc−/− double mutants. Compared with young wild-type (WT) mice, micro-computerized tomography analysis revealed that young Terc−/− and Wrn−/−Terc−/− mice have decreased trabecular bone volume, trabecular number and trabecular thickness, as well as increased trabecular spacing. In cortical bone, young Terc−/− and Wrn−/−Terc−/− mice have increased cortical thinning, and increased porosity relative to age-matched WT mice. These trabecular and cortical changes were accelerated with age in Terc−/− and Wrn−/−Terc−/− mice compared with older WT mice. Histological quantification of osteoblasts in aged mice showed a similar number of osteoblasts in all genotypes; however, significant decreases in osteoid, mineralization surface, mineral apposition rate and bone formation rate in older Terc−/− and Wrn−/−Terc−/− bone suggest that osteoblast dysfunction is a prominent feature of precocious aging in these mice. Except in the Wrn−/− single mutant, osteoclast number did not increase in any genotype. Significant alterations in mechanical parameters (structure model index, degree of anistrophy and moment of inertia) of the Terc−/− and Wrn−/−Terc−/− femurs compared with WT mice were also observed. Young Wrn−/−Terc−/− mice had a statistically significant increase in bone-marrow fat content compared with young WT mice, which remained elevated in aged double mutants. Taken together, our results suggest that Terc−/− and Wrn−/−Terc−/− mutants recapitulate the human bone aging phenotype and are useful models for studying age-related osteoporosis.